2018
DOI: 10.1111/odi.12767
|View full text |Cite
|
Sign up to set email alerts
|

Role of tissue‐specific steroid metabolism in oral disease: Is there any clinical implication?

Abstract: The discovery of an oral glucocorticoid system has provided novel conceptual frameworks for understanding the effects of endogenous and exogenous corticosteroids in the oral cavity. For example, liquorice derivatives have long been used in the treatment of oral inflammatory conditions and it is now known that a chief constituent of liquorice root, glycyrrhetinic acid, inhibits 11β-hydroxysteroid dehydrogenase (11β-HSD) type 2 thus increasing local cortisol levels. Hence, targeting the local interconversion bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…AMPK, HIF-1 signaling pathways and Glucose metabolism are widely recognized and heavily pursued for treatment of metabolic diseases, such as a variety of cancers [34][35][36][37]. Previous reports have demonstrated that the increased hormones occurred as cause of tongue cancer progression and revealed the components of the steroid biosynthetic pathways can be considered to be cancer biomarkers [38][39][40][41]. Thus, the enrichment of LEPR, PFKM, PGK1, and CYP19A1 in the aforementioned pathways suggests these prhRBPs as potential therapeutic targets.…”
Section: Prognosis-related Hub Rbps Regulate Cancer Metabolic Processesmentioning
confidence: 99%
“…AMPK, HIF-1 signaling pathways and Glucose metabolism are widely recognized and heavily pursued for treatment of metabolic diseases, such as a variety of cancers [34][35][36][37]. Previous reports have demonstrated that the increased hormones occurred as cause of tongue cancer progression and revealed the components of the steroid biosynthetic pathways can be considered to be cancer biomarkers [38][39][40][41]. Thus, the enrichment of LEPR, PFKM, PGK1, and CYP19A1 in the aforementioned pathways suggests these prhRBPs as potential therapeutic targets.…”
Section: Prognosis-related Hub Rbps Regulate Cancer Metabolic Processesmentioning
confidence: 99%
“…Tissue cortisol level is regulated by 11-β-hydroxysteroid dehydrogenases (11-β-HSDs) 1 and 2; 11-β-HSD1 metabolizes cortisone (inactive) to cortisol, which can be converted back to cortisone by 11-β-HSD2. Figure 1 summarizes some of the reported features of the glucocorticoid system in oral tissues [ 10 , 11 ]. Indeed, the demonstration of a reduction in 11-β-HSD2 expression in oral squamous cell carcinoma (SCC) has focused attention on the role of local generation of glucocorticoids in oral tissue pathologies [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 summarizes some of the reported features of the glucocorticoid system in oral tissues [ 10 , 11 ]. Indeed, the demonstration of a reduction in 11-β-HSD2 expression in oral squamous cell carcinoma (SCC) has focused attention on the role of local generation of glucocorticoids in oral tissue pathologies [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations